2011
DOI: 10.1002/ejsp.723
|View full text |Cite
|
Sign up to set email alerts
|

Predicting support for racial transformation policies: Intergroup threat, racial prejudice, sense of group entitlement and strength of identification

Abstract: Policies and programs designed to challenge the effects of racial discrimination (such as affirmative action) are hotly contested. Factors which have been proposed to explain opposition to these policies include racial prejudice, group threat and self-interest, and perceptions of intergroup justice. We report the results of two random national telephone surveys which tested a theoretically based model of the predictors of policy support in post-apartheid South Africa. The results provided limited support for B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 64 publications
3
45
1
Order By: Relevance
“…Perceived differences between the ingroup and outgroup constitute another aspect of symbolic threat (Aberson, 2015;Durrheim et al, 2011;Stephan, Diaz-Loving, & Duran, 2000).…”
Section: Intergroup Threat From Gay People and The Romamentioning
confidence: 99%
“…Perceived differences between the ingroup and outgroup constitute another aspect of symbolic threat (Aberson, 2015;Durrheim et al, 2011;Stephan, Diaz-Loving, & Duran, 2000).…”
Section: Intergroup Threat From Gay People and The Romamentioning
confidence: 99%
“…Black people are more strongly in favor of policies directed at transformation and integration than other groups. Whites are most opposed to policies such as affirmative action, land redistribution, and racial quotas in sports teams, and this policy opposition is strongly related to racial prejudice and to threat perceptions (Durrheim, 2003; Durrheim et al, in press). In a qualitative study, Durrheim and Dixon (2005) also found that Black and White perceptions of desegregation were rooted in a sense of threat among Whites: “The form that desegregation has taken, with Blacks entering previously exclusive White spaces, is experienced as loss by Whites but as gain by Blacks” (p. 169).…”
mentioning
confidence: 99%
“…Specifically, Wohl, Giguere, Branscombe, and McVicar (2011) showed that identification with a group whose distinctiveness might be lost in the future increased the effects of threat upon endorsement of ingroup protective action. Durrheim, Dixon, Tredoux, Eaton, Quayle, and Clack (2011) found that among Black respondents, high levels of threat and ingroup identification were associated with support for racial transformation policies, whereas among White respondents, low levels of threat and prejudice predicted their support for affirmative actions. Costello and Hodson (2011) further illustrate that the relation between threat and solidarity-based action (empowerment and assistance of immigrants) depends on individual's social dominance orientation (SDO): Higher SDO predicted greater resistance to assist immigrants upon exposure to realistic or symbolic threats.…”
Section: Psychological Implications Of the Social Structurementioning
confidence: 93%